Split Liver Transplantation and Pediatric Waitlist Mortality in the United States: Potential for Improvement. Issue 3 (March 2019) - Perito, Emily R.; Roll, Garrett; Dodge, Jennifer L.; Rhee, Sue; Roberts, John P.
Abstract : Background: In the United States, 1 in 10 infants and 1 in 20 older children die on the liver transplant waiting list. Increasing split liver transplantation could increase organ availability for these children, without decreasing transplants in adults. Methods: Using United Network for Organ Sharing Standard Transplant Analysis and Research data, we identified livers transplanted 2010 to 2015 that could potentially have been used for split transplant, based on strict criteria. Livers not suitable for pediatric patients or allocated to high-risk recipients were excluded. Number and distribution of potentially "split-able" livers were compared to pediatric waitlist deaths in each region. Results: Of 37 333 deceased donor livers transplanted, 6.3% met our strict criteria for utilization in split liver transplant. Only 3.8% of these were actually utilized for split liver transplantation. 96% were used for a single adult recipient. Of the 2253 transplanted as whole livers, 82% of their recipients were listed as willing to accept a segmental liver, and only 3% were listed as requiring a cold ischemia time less than 6 hours. Over the same 5 years, 299 children died on the waitlist. In every United Network for Organ Sharing region, there were more potentially "split-able" livers than pediatric waitlist deaths. Thirty-seven percent of pediatric waitlist deaths occurred at transplant centers that averaged 1 or less pediatric split liver transplantation annually during the study period. Conclusions: This comparison, although not conclusive, suggests that we might be missing opportunities to reduce pediatric waitlist mortality without decreasing access for adults—using split liver transplant. Barriers are significant, but further work on strategies to increase split liver transplant is warranted. Abstract : Supplemental Digital Content is available in the text.